Public Participation in South Africa’s Policy Decision-Making Process: The Mass and the Elite Choices - Mokoko Piet Sebola (Central European Public Administration Review)
Public participation in policy-making dominates most Development, Political Science and Public Administration academic discourses. The issue of concern is the extent to which governments are able to create structures that allow for public participation of citizens in matters affecting their political and developmental concerns. The success of any government administration is, therefore, measured on the basis of how the citizens participate and contribute to the process of deciding their own political and developmental direction. It is argued that the public participation approach that considers the interests, contributions and needs of citizens in policy decision-making processes is difficult in practice. This article investigates the processes of public participation in public policy-making in South Africa with respect to the Choice on Termination of Pregnancy Act 92 of 1996, the Abolition of Capital Punishment policy and the Civil Union Act 17 of 2006. This is done with a view to determine if public participation in policy decision-making is a reflection of the choices of the elite or the masses.